Functional constipation in children - N. L. Pakhomovskaya; O. F. Tatianina; T. Yu. Lazareva (Медицинский совет, 2022)
Constipation is one of the most common nosologies that a pediatric gastroenterologist deals with during outpatient visits. In the vast majority of children with constipation the problem is functional in nature. According to studies published in the Russian Federation, the frequency of constipation in children accounts for about 25–30%. The joint clinical guidelines of the European and North American Societies of Pediatric Gastroenterologists, Hepatologists and Nutritionists for the management of children with functional constipation were published in 2014. The national guidelines for the diagnosis and treatment of functional constipation are based on these guidelines. According to the clinical guidelines, the 2006 Rome III criteria should be used to establish the diagnosis of functional constipation in children. In May 2016, the Rome IV criteria that provide separate diagnostic criteria for infants and children under 4 years of age and children over 4 years and teenagers were adopted. A group of children with symptoms of constipation, who have already had toilet skills at the time of diagnosis, was identified among infants and children under 4 years of age. The presence of anxiety symptoms or refractory constipation (constipation that does not resolve within 3 months while taking adequate therapy) is considered an indication for use of additional examination methods, including instrumental ones. The manifestation of constipation is often associated with a change in eating habits - the period of introduction of complementary feeding in infants or the beginning of going to a day-care centre, inadequate fluid intake. The onset of constipation often coincides with the period of the development of hygiene skills (potty training). The voluntary stool retention by a child who is trying to avoid painful defecation experiences is the main mechanism for the development of constipation. The aim of functional constipation treatment is to soften the stools, which facilitates painless defecation and ensure that there is an urge to defecate. Clinical examples of the treatment of patients with functional constipation and chronic colonic stasis, functional constipation and encopresis are provided. The outcome of the treatment of functional constipation is to ensure painless defecation and the development of a stable defecation reflex. The drug therapy for functional constipation is based on the use of laxatives. Dietary advice and behavioral therapy also play an important role.